City Clerk gets deserved praise (Raton Range Raton, New Mexico, 1983)
Newspaper article on Eva Mae Sproule the City Clerk for Raton, New Mexico and the Praise she received from Auditor Dixon Waller.
Master list item #: 2
File location is in the Raton file Cabinet
Keywords: Dixon; Sproule, Eva Mae; Waller, Gary; City Clerk; Waller and Company; Local History; Biography; Recognition; accounting; City Employees; Raton, New Mexico